LA LINTERNA MÁGICA COMO SOPORTE PUBLICITARIO. RECORRIDO HISTÓRICO POR NOTICIAS, ANÉCDOTAS Y PATENTES - Dra. María Begoña SÁNCHEZ GALÁN, (Fonseca, Journal of Communication, 2023)
The magic lantern, the device in which we can find the origins of the current audio-visual culture, was also the cradle of media advertising. During the last decades of the 19th Century, in an attempt to face the growing advertising saturation that was already visible in the dairy press and on the walls of big cities, the advertisers, projectionists and a large group of inventors, began to turn to the magic lantern as a means for exhibiting all kind of advertisements.